2003
DOI: 10.1128/aem.69.11.6908-6922.2003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Characterization, and Loci of the tuf Genes in Lactobacillus and Bifidobacterium Species and Their Direct Application for Species Identification

Abstract: We analyzed the tuf gene, encoding elongation factor Tu, from 33 strains representing 17 Lactobacillus species and 8 Bifidobacterium species. The tuf sequences were aligned and used to infer phylogenesis among species of lactobacilli and bifidobacteria. We demonstrated that the synonymous substitution affecting this gene renders elongation factor Tu a reliable molecular clock for investigating evolutionary distances of lactobacilli and bifidobacteria. In fact, the phylogeny generated by these tuf sequences is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
123
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 55 publications
1
123
1
3
Order By: Relevance
“…As suggested by Ventura et al, 16 the low rate of 16S rDNA gene evolution is often responsible for the failure in identification of highly related bacterial species. In this scenario, the polyphasic taxonomy suggested by Vandamme et al 31 and by other authors, 17,18,32 is the better choice for bacterial identification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As suggested by Ventura et al, 16 the low rate of 16S rDNA gene evolution is often responsible for the failure in identification of highly related bacterial species. In this scenario, the polyphasic taxonomy suggested by Vandamme et al 31 and by other authors, 17,18,32 is the better choice for bacterial identification.…”
Section: Discussionmentioning
confidence: 99%
“…The probiotic strain used in product III is indicated by depositor as L. casei DG (CNCM I-1572) and is considered sufficiently characterized by EFSA Panel on Dietic Products, Nutrition and Allergies (NDA). 27 However, our study, using multiplex PCR 15 and tuf gene amplification, 16 not used by depositor, identified the strain as L. paracasei. In fact, tuf gene is an important molecular marker to distinguish so related taxa as L. casei group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR conditions and primers for amplification of fusA, rplB and gyrB gene sequences were taken from Delétoile et al (2010). Similarly, conditions for amplification of xfp, tuf, rpoC and dnaK are mentioned in previous studies (Ventura et al, 2003(Ventura et al, , 2005(Ventura et al, , 2006Berthoud et al, 2005). PCR products were then checked, purified and sequenced as described above.…”
mentioning
confidence: 99%